Perceived Usefulness of a Microfinance Intervention on Health Awareness and Practices in Nepal - Dhungana, Bharat Ram; Singh, Jitendra Kumar; Acharya, Dilaram; Gautam, Salila; Paudyal, Pravin (Frontiers in Public Health, 2016)
Background: Economic constraints may lead to poor health among people from the developing world. Microfinance has proven to be useful in improving health outcomes elsewhere, but it still remains a neglected issue in Nepal. This study aims assess perceived usefulness of the microfinance on health awareness and practices among different ethnic groups of Nepal. Method: A community-based cross-sectional study was conducted in four districts of western Nepal. A total of 500 microfinance clients representing different ethnic groups (upper caste, aadibasi and janajati, and dalit) were selected by using systemic random sampling. Health awareness and practices among different ethnic groups were compared by logistic regression after adjustment for age, level of education, sex of household heads, occupation and place of residence. Since participants were asked about their health awareness and practices, before and after microfinance intervention, during a single interview, there was a strong possibility of recall bias with respect to their pre-intervention awareness and other measures. Results: Microfinance intervention positively influenced self-reported health awareness and practices among different ethnic groups in Nepal; which was highest among the upper caste group (77-92%, rate ratios around 1.7 - 2.6), followed by the aadibasi/janajati(60-76%, rate ratios around 1.4-1.8) and dalit group (33-52%, reference group). Self-reported awareness about environment and sanitation, family planning methods and available health services at local level improved from 11.2% to 69.2%, 9.2% to 65.0%, and 3.8% to 59.8% respectively among the clients after microfinance intervention (p<0.001). Similarly, the practices of eating nutritious food/balanced diet, drinking safe water, using toilet, immunizing the children, and regularly visiting the healthcare facility were improved from 4.2% to 63.8%, 12.6% to 66.8%, 15.2% to 70.4%, 15.8% to 73.8%, and 3.6% to 61.4% respectively (p<0.001). Conclusions: Despite lack of control group and potential recall bias, this study reports positive effect of microfinance on self-reported health awareness and practices among different ethnic groups of Nepal. This finding supports further implementation and evaluation of equity-based microfinance to improve health and economic conditions of Nepalese people.